12x+8=5x+36

Simple and best practice solution for 12x+8=5x+36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+8=5x+36 equation:


Simplifying
12x + 8 = 5x + 36

Reorder the terms:
8 + 12x = 5x + 36

Reorder the terms:
8 + 12x = 36 + 5x

Solving
8 + 12x = 36 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
8 + 12x + -5x = 36 + 5x + -5x

Combine like terms: 12x + -5x = 7x
8 + 7x = 36 + 5x + -5x

Combine like terms: 5x + -5x = 0
8 + 7x = 36 + 0
8 + 7x = 36

Add '-8' to each side of the equation.
8 + -8 + 7x = 36 + -8

Combine like terms: 8 + -8 = 0
0 + 7x = 36 + -8
7x = 36 + -8

Combine like terms: 36 + -8 = 28
7x = 28

Divide each side by '7'.
x = 4

Simplifying
x = 4

See similar equations:

| 5(x-1)=-35 | | z^2-50i=0 | | -0.7c=-16.1 | | 10(x-6)=-147 | | 15-x^2=3x+5 | | 9x-2.3x-3=0 | | 9.7-m=2.8 | | 9-.5x=2 | | 6(x+1)=-18 | | 9-3x=-6x+3 | | 9x+6=3(2-x) | | 5x+2+5x+1=30 | | 6-5x=-x-2 | | x+5*3=36 | | -3(3x-7)=5(3x+1) | | 3(3x-7)=5(3x+1) | | 3(3x+6)=135 | | 8(2x+9)=120 | | .66x-4=-1 | | 6y+6=y-2 | | 1g(x+7)+1g(3x+1)=2 | | (-2)=4x+2 | | (x-3)*7=70 | | 0.05x=150 | | .66x-4=1 | | -4x+9x-(-4)=12x-5-(-10) | | 4y(5y-8)+24y= | | (x-10)*4=24 | | 2(4x-5)=12 | | x^2+2logX+94.3=0 | | (x+5)*6=54 | | (-3)=x^2-5 |

Equations solver categories